2021
DOI: 10.1101/2021.03.02.433577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PP2A/B55α substrate recruitment as defined by the retinoblastoma-related protein p107

Abstract: Protein phosphorylation is a reversible post-translation modification essential in cell signaling. This study addresses a long-standing question as to how the most abundant serine/threonine Protein-Phosphatase 2 (PP2A) holoenzyme, PP2A/B55α, specifically recognizes substrates and presents them to the enzyme active site. Here, we show how the PP2A regulatory subunit B55α recruits p107, a pRB-related tumor suppressor and B55α substrate. Using molecular and cellular approaches, we identified a conserved region 1(… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…6D-I). In addition, PPP2R2A D197 was previously reported to be a key site for Tau and P107 recruitment [42,43], suggesting PPP2R2A D197 might serve as a conserved pivotal amino acid in mediating PPP2R2A substrate recognition. This acidic top may use substrate specific sequences to distinguish its different binding partners, and the PPP2R2A D197 or/and PPP2R2A N181 may be key recognition sites for multiple substrates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…6D-I). In addition, PPP2R2A D197 was previously reported to be a key site for Tau and P107 recruitment [42,43], suggesting PPP2R2A D197 might serve as a conserved pivotal amino acid in mediating PPP2R2A substrate recognition. This acidic top may use substrate specific sequences to distinguish its different binding partners, and the PPP2R2A D197 or/and PPP2R2A N181 may be key recognition sites for multiple substrates.…”
Section: Discussionmentioning
confidence: 97%
“…PP2A is a critical Ser/Thr protein phosphatase that relies on its B-regulatory subunits to specifically recruit substrates [42,44,45]. Previous reports have highlighted that PPP2R2A may perform different functions due to the potential presence of different substrate recruitment sites [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated p107 is a known substrate for PP2A/B55a [17][18][19], and IER5 enhances p107 dephosphorylation by PP2A. The B55a subunit binds to the 'spacer region' between pockets A and B of p107 [51], whereas IER5 binds to the N-and C-terminal regions. The multiple interactions of IER5-PP2A/B55 and p107 enhance PP2A activity towards p107.…”
Section: Discussionmentioning
confidence: 99%
“…For the B55 regulatory subunit it was shown that basic residues flanking a minimal CDK consensus sequence promoted B55 dephosphorylation [ 15 , 19 ]. However, a 20 amino acid polybasic region containing three arginine residues was identified as crucial for PP2A-B55 binding to mCRTC3 and recently a short linear motif (HxRVxxV) could be identified as mediator of B55α binding in p107, a member of the Retinoblastoma tumor suppressor protein family [ 20 , 21 ]. SLFN5 contains only a single small basic motif (RKRK) at its C-terminus and some additional pairs of basic amino acids which are distributed along the protein.…”
Section: Discussionmentioning
confidence: 99%